Feral Pigeon Ecology and Zoonoses in Stevens Point, Wisconsin - Krakowski, James (University of Wisconsin-Stevens Point, College of Natural Resources, 1982)
Feral pigeons (Columba livia) in Stevens Point, Wisconsin were monitored for ecological parameters and zoonoses from June 1976 through September 1977. A relatively stationary population of 900 pigeons was found to use 112 roosting sites within the city. Eight large communal roosts harbored 70% of the population. Pigeons nesting in 2 communal roost sites were more prolific than a sample of house roosting pigeons, which roosted in single pairs. An estimated annual increment of 43% was obtained by expanding productivity values from a sample of communal and house nesting sites. June was the peak month for egg laying and fledging. Hatching success was 71%; this was as well as or better than that reported elsewhere. Human factors were the greatest cause of mortality. The main food source for the Stevens Point pigeon population was the Soo Line railroad tracks, where the birds fed on grain spilled from railway cars. The pigeons were relatively healthy; Chlamydia antibodies were found in 21% of 103 blood samples and was the only zoonosis found. The feral pigeon was found to be a nuisance by only 37% of the people in Stevens Point. The pigeon population should not be exterminated, but should be managed to preclude large concentrations. Management could be accomplished by eliminating large roosts and adapting procedures at the Soo Line railroad tracks to lessen the feral pigeon food supply.